Factor Reallocation and Growth in Developing Countries - Poirson, Helene (IMF Working Papers; Working Paper, 2000)
This paper examines the extent to which developing countries benefit from intersectoral factor transfers by specifying the impact and determinants of sectoral changes and of the degree of dualism (or allocation inefficiency) in a dual economy model. Conditions under which factor reallocation is growth-enhancing are derived. An empirical error-correction equation is estimated for 30 developing countries during 1965-80. Results suggest that labor reallocation effects are especially important in countries with high rates of investment (and thus high rates of labor transfer) and/or at low levels of development (and thus high degrees of dualism).